2010
DOI: 10.1039/b923548e
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 doping by hydroxyurea at the nucleation stage: towards a new photocatalyst in the visible spectral range

Abstract: We report an original method of preparation of OCN-doped TiO 2 for photocatalysis in the visible spectral range. The preparation is achieved by a sol-gel route using titanium tetraisopropoxide precursor. Special attention was paid to fluid micromixing, which enables homogeneous reaction conditions in the reactor bulk and monodispersity of the produced clusters/nanoparticles. The dopant hydroxyurea (HyU, CH 4 N 2 O 2 ) is injected into the reactive fluid at the nucleation stage, which lasts tens of milliseconds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
(88 reference statements)
4
18
0
Order By: Relevance
“…No differences between samples are noticeable in the Ti 2 p area. Indeed, the shift to a slightly lower binding energy induced by a change in the titanium chemical environment (as in the case of Ti–O–N bonding) would be too small to be distinguished from the main peak [ 47 ]. On the other hand, the systematic absence of a peak around 455–456 eV excludes the presence of Ti–N species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No differences between samples are noticeable in the Ti 2 p area. Indeed, the shift to a slightly lower binding energy induced by a change in the titanium chemical environment (as in the case of Ti–O–N bonding) would be too small to be distinguished from the main peak [ 47 ]. On the other hand, the systematic absence of a peak around 455–456 eV excludes the presence of Ti–N species.…”
Section: Resultsmentioning
confidence: 99%
“…For each sample, the O 1 s (530 eV)/Ti 2p ratio is close to 2, corresponding to stoichiometric TiO 2 . The two other components at higher binding energy are complicated to attribute, as they correspond to oxygen bonded to carbon due to carbon contamination and/or nitrogen bonding (N–O–Ti, N=O) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the dried gels prepared with urea have included nitrogen as shown in Tables 3(a) and (c). According to the literatures [48]- [50], it has been reported that urea coordinates to titanium through weak C=O → Ti coordination bonding with remaining the carbonyl groups. Therefore, it was expected that the sites coordinated by urea are easy to be hydrolyzed by H 2 O.…”
Section: Formation Mechanism Of Carbon-containing Tiomentioning
confidence: 99%